Fusobacterium necrophorum intratonsillar abscess as a source of bacteremia in a patient with a history of substance abuse - Nanu, Claudiu; Ciocan, Liana Adela; Radu, Georgiana; Sumedrea, Liliana; Popescu, Gabriel Adrian; Borcan, Alina Maria (The Journal of Infection in Developing Countries, 2024)
A 22-year-old male, with a history of recreational drug use, was admitted with a 24-hour history of sore throat, bilateral otalgia, fever, chills, sweats, and pain in the upper chest. The blood cultures were positive for Fusobacterium necrophorum. A thoracic and neck soft tissue computed tomography (CT) scan revealed an intratonsillar abscess and pulmonary septic emboli. Initial treatment with Piperacillin-tazobactam and Clindamycin was de-escalated after 5 days. The patient made a complete recovery after 22 days of antibiotic treatment.